Identifying key variables to support the development of a composite index to measure the socio-economic contributions of IBFC on the development of Labuan - Rosita Chong; Ho, Chong Mun; Chia, Ricky Chee Jiun (Universiti Malaysia Sabah, 2013)
The study provides some very interesting findings on the assessment of the socio economic impacts with the creation of Labuan as an International Business Rnancial c.entre. Since its establishment as an IOFC in 1990 and later rebranded as Labuan International Business and Financial c.entre (IBFC) in 2007. This study attempts to identify key variables that can be used to measure the socio-economic contributions of IBFC on the development of Labuan. Labuan IBFC has shown some socio-economic impacts on the development of Labuan. A composite index was developed to access these impacts. During the early inception of Labuan IBFC, the composite index was below the zero. However, starting from year 2003, it is observed that the socio economic impacts were above the zero mean. In other words, Labuan IBFC has a positive socio-economic impact on the Labuan community starting from year 2003 till 2010. It could also be seen that the index is ranked highest in year 2010, follows by year 2009 and 2008. This suggests that the success of Labuan IBFC in achieving its principal objective to develop the economy of Labuan as weU as the well-being of its community. In summary, the promotion of Labuan IBFC has not only successfully increased the business activities in Labuan, but also improved the living standard of Labuan community.